Copper, lead and zinc removal from metal-contaminated wastewater by adsorption onto agricultural wastes - Suthee Janyasuthiwong (2018)
© 2015 Taylor & Francis. The use of agricultural wastes (groundnut shell, orange and banana peel, rice husk, coconut husk and Wawa tree saw dust) as potential cost-effective adsorbent for heavy metal removal from wastewater was evaluated. The effect of pH (2.0-6.0), adsorbent dosage (0.6-2.2 g), contact time (10-130 min) and initial concentration (Pb: 5-105 mg/L, Cu and Zn: 2.5-52.7 mg/L) on the metal removal efficiency and uptake capacity were investigated using response surface methodology to optimize the process conditions. Groundnut shell showed a high potential to remove Cu, Pb and Zn from synthetic wastewater. The highest removal efficiencies with groundnut as the adsorbent were 85% at pH 5.0 for Cu and 98% at pH 3.0 for Pb and Zn. The optimum conditions obtained were 2.5 g adsorbent with 40.7 mg/L Cu at pH 4.4 and 64 min contact time, 2.5 g adsorbent with 196.1 mg/L Pb at pH 5.6 and 60 min contact time and 3.1 g adsorbent with 70.2 mg/L Zn at pH 4.3 and 50 min contact time, for Cu, Pb and Zn, respectively. The regeneration of the groundnut shell was possible for a maximum of three cycles using 0.2 M HCl as the desorbing solution without any significant change in the adsorbing efficiency.